The Effectiveness of Kaili Folktales to Improve Students Reading Comprehension at SMPN 19 Palu - Majeed, Maryana; Mukrim, Mukrim; Lebagi, Desrin; Manurung, Konder (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the effectiveness of Kaili folktales in enhancing students’ reading comprehension at SMPN 19 Palu. The research was motivated by students' difficulties in understanding narrative texts, reflecting low reading comprehension levels. A quasi-experimental design was employed, involving 43 eighth-grade students divided into an experimental group (n = 23) and a control group (n = 20). The experimental group was taught using Kaili folktales, while the control group used general folktales. Data were collected through pre-tests and post-tests consisting of multiple-choice and essay questions. The results revealed that the experimental group achieved a higher average post-test score (71.04) compared to the control group (61.35). A Mann-Whitney test using SPSS 26 yielded a Sig. (2-tailed) value of 0.001, indicating a significant difference between the groups. The findings suggest that incorporating Kaili folktales into English instruction effectively enhances students’ reading comprehension.